2024
DOI: 10.3389/fphar.2024.1398381
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-associated endoplasmic reticulum membranes as a therapeutic target for cardiovascular diseases

Yanqiu Ding,
Nanyang Liu,
Dawu Zhang
et al.

Abstract: Cardiovascular diseases (CVDs) are currently the leading cause of death worldwide. In 2022, the CVDs contributed to 19.8 million deaths globally, accounting for one-third of all global deaths. With an aging population and changing lifestyles, CVDs pose a major threat to human health. Mitochondria-associated endoplasmic reticulum membranes (MAMs) are communication platforms between cellular organelles and regulate cellular physiological functions, including apoptosis, autophagy, and programmed necrosis. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 132 publications
0
1
0
Order By: Relevance
“…On the basis of these observations, we support that MFN2 plays a key role in restoring mitochondrial function in HG-induced HLE-B3 cells. In addition, mitochondria and endoplasmic reticulum (ER) are distinct organelles that physically interact with each other, including exchange of phospholipids, calcium and other metabolites to maintain cellular integrity and bioenergetics [31][32][33]. Previous studies have reported that MFN2 promotes the contact of mitochondria and ER [32,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these observations, we support that MFN2 plays a key role in restoring mitochondrial function in HG-induced HLE-B3 cells. In addition, mitochondria and endoplasmic reticulum (ER) are distinct organelles that physically interact with each other, including exchange of phospholipids, calcium and other metabolites to maintain cellular integrity and bioenergetics [31][32][33]. Previous studies have reported that MFN2 promotes the contact of mitochondria and ER [32,34,35].…”
Section: Discussionmentioning
confidence: 99%